2018
DOI: 10.3897/rrpharmacology.4.27221
|View full text |Cite
|
Sign up to set email alerts
|

Imidazoline receptors agonists: possible mechanisms of endothelioprotection

Abstract: Imidazoline receptor agonists are one of the groups of contemporary antihypertensive drugs with the pleiotropic cardiovascular effects. In this review, the historical, physiological, pathophysiological aspects concerning imidazoline receptor agonists and possible mechanisms for their participation in endothelioprotection were considered. Illuminated the molecular biology of each subtype of imidazoline receptors and their significance in the pharmacological correction of cardiovascular disease. IR typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…Table 4 summarizes the most relevant results obtained in pharmacological studies related to the antihyperglycemic effect of TT. Alkaloids could act synergistically with the steroidal saponins, as it was shown that imidazolidine derivatives stimulate insulin secretion by activation of imidazoline receptor type 3 binding sites in the pancreatic beta cells [103].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Table 4 summarizes the most relevant results obtained in pharmacological studies related to the antihyperglycemic effect of TT. Alkaloids could act synergistically with the steroidal saponins, as it was shown that imidazolidine derivatives stimulate insulin secretion by activation of imidazoline receptor type 3 binding sites in the pancreatic beta cells [103].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…M odern pharmacology has a wide arsenal of compounds with cytoprotective potential. [1,2] In accordance with the requirements of esthetic and cosmetic medicine, the development of dermatotropic agents with woundhealing activity is actively conducted. One of these tools is a gel based on bischofite, a natural mineral with significant reserves in the territory of the Lower Volga region.…”
Section: Introductionmentioning
confidence: 99%
“…Поиск новых лекарственных препаратов для лечения и профилактики заболеваний является актуальной задачей современной фармакологии [5,6,19]. Одним из таких направлений является создание лекарственных препаратов для лечения и профилактики преэклампсии [1,4].…”
unclassified